2013
DOI: 10.1088/1674-1056/22/7/076701
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial characteristics of Al/Al2O3/ZnO/n-GaAs MOS capacitor

Abstract: The interfacial characteristics of Al/Al 2 O 3 /ZnO/n-GaAs metal-oxide-semiconductor (MOS) capacitor are investigated. The results measured by X-ray photoelectron spectroscopy (XPS) and high-resolution transmission electron microscopy (HRTEM) show that the presence of ZnO can effectively suppress the formations of oxides at the interface between the GaAs and gate dielectric and gain smooth interface. The ZnO-passivated GaAs MOS capacitor exhibits a very small hysteresis and frequency dispersion. Using the Term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…The Ga-O bond/As segregation near the interface and the trapping of carriers near the valence band edge was significantly suppressed, greatly improving the C-V characteristics on p-type GaAs substrates, as shown in Figure 7. Similar results were reported by Liu Chen et al [35], who found deposition of ZnO prior to Al2O3 gate materials deposition directly can further reduce the interface trap density. The n-GaAs MOSCAP with 2 nm ALD ZnO interface passivation layer exhibited higher accumulation capacitance and a very small C-V dispersion and hysteresis.…”
Section: Passivation Film Depositing By Atomic Layer Deposition (Ald)supporting
confidence: 89%
See 1 more Smart Citation
“…The Ga-O bond/As segregation near the interface and the trapping of carriers near the valence band edge was significantly suppressed, greatly improving the C-V characteristics on p-type GaAs substrates, as shown in Figure 7. Similar results were reported by Liu Chen et al [35], who found deposition of ZnO prior to Al2O3 gate materials deposition directly can further reduce the interface trap density. The n-GaAs MOSCAP with 2 nm ALD ZnO interface passivation layer exhibited higher accumulation capacitance and a very small C-V dispersion and hysteresis.…”
Section: Passivation Film Depositing By Atomic Layer Deposition (Ald)supporting
confidence: 89%
“…Lucero et al used ALD to format a ZnO/ZnS IPL by converting an (NH4)2S cleaned p-In0.53Ga0.47As with diethylzinc and water [37]. Diethylzinc reacted with S and O on the InGaAs, Similar results were reported by Liu Chen et al [35], who found deposition of ZnO prior to Al 2 O 3 gate materials deposition directly can further reduce the interface trap density. The n-GaAs MOSCAP with 2 nm ALD ZnO interface passivation layer exhibited higher accumulation capacitance and a very small C-V dispersion and hysteresis.…”
Section: Passivation Film Depositing By Atomic Layer Deposition (Ald)mentioning
confidence: 64%
“…It is noted that the increased EOT would degrade the gate control ability of the device. The equivalent dielectric constant ε OX was calculated according to the C-V test data [18]. The two samples with a HfO 2 /Al 2 O 3 laminated dielectric have lower ε OX values than the sample with only a HfO 2 dielectric, and the ε OX value decreases as the thickness of the Al 2 O 3 film increases.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, there are three highly accepted mechanisms for the morphogenesis of ZnO-Ts: (1) that involving the formation of a stable zinc-blende core and subsequent growth of wurtzite legs [38,39]; (2) the model based on a transformation of a zinc-blende embryo into a wurtzite twined nucleus [40,41]; and (3) the octahedral multiple twin nucleus model (octa-twin model) [27,[42][43][44]. Several arguments have been provided in favor and against each model; however, the octa-twin model is the proposal which complies with thermodynamic constrains and successfully explains the different sets of the interleg angles observed in a variety of ZnO-Ts [45]. In addition, other formation mechanisms have been proposed [28], nevertheless, they seem unreliable and poor empirical evidence has been provided to support them.…”
Section: Resultsmentioning
confidence: 99%